Advanced Force Coordination of Lower Extremities During Visuomotor Control Task in Soccer Players - Lee, Tae Lee; Ko, Do-Kyung; Kang, Nyeonju (Research quarterly for exercise and sport, 2024)
Purpose: This study is aimed to determine specific bilateral lower extremity motor performances and coordination patterns in soccer players with healthy controls using the bilateral force control paradigm. We hypothesized that soccer players would show more advanced bilateral force control performances than untrained controls. Methods: Participants were 13 university soccer players and 13 healthy controls. Each group performed bilateral ankle dorsiflexion force control tasks across two vision conditions (i.e., vision and no-vision) and two targeted force levels (i.e., 10% and 40% maximum voluntary contraction). We calculated force accuracy, variability, and symmetry to assess force control performances. To estimate bilateral force coordination, we calculated Pearson's correlation coefficients between feet-within a single trial and considered uncontrolled manifold variables across multiple trials. In the no-vision condition, we performed secondary analyses for initial force control patters after removal of visual feedback. Results: There were no significant group differences in bilateral force accuracy and variability but, compared to the control group, soccer players showed higher force symmetry between left and right ankle dorsiflexion forces. For force coordination between feet, soccer players revealed more negative values of the correlation coefficient and greater good variability from the uncontrolled manifold analysis than those for the control group. The secondary analysis revealed no significant group differences in the time until force drift and amount of force adjustments. Conclusions: Soccer players have more compensatory and flexible interlimb force coordination strategies between feet.